CSPα in neurodegenerative diseases - Huang, Liqin; Zhang, Zhaohui (Frontiers in Aging Neuroscience, 2022)
Adult-onset neuronal ceroid lipofuscinosis (ANCL) is a rare neurodegenerative disease characterized by epilepsy, cognitive degeneration, and motor disorders caused by mutations in the DNAJC5 gene. In addition to being associated with ANCL disease, the cysteine string proteins α (CSPα) encoded by the DNAJC5 gene have been implicated in several neurodegenerative diseases such as Alzheimer's disease (AD), Parkinson's disease (PD), and Huntington's disease. However, the pathogenic mechanism responsible for these neurodegenerative diseases has not yet been elucidated. Therefore, this study examines the functional properties of the CSPα protein and the related mechanisms of neurodegenerative diseases.